Coloproctology - Herold, Alexander; Lehur, Paul-Antoine; Matzel, Klaus E.; O'Connell, P. Ronan (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book offers up-to-date coverage of the full range of topics in coloproctology: anatomy, physiology, anal disorders, dermatology, functional disorders, inflammatory bowel disease, endometriosis, appendicitis, benign and malignant tumors, presacral tumors, laparoscopy, endoscopy, perioperative management, intestinal failure, abdominal wall reconstruction, emergencies, and pain syndromes. Each of the chapters on individual disorders provides a comprehensive overview on etiology, incidence, epidemiology, diagnostics, medical and surgical treatment, access, complications, and special considerations. In presenting data, care is always taken to refer to the best available level of evidence. The book forms the latest addition to Springer's European Manual Medicine series and is the second edition of Coloproctology. It will be the first standard recommended textbook of the European Society of Coloproctology. The editors have again assembled a group of experienced authors, each of whom has an international reputation within coloproctology or an allied specialty and a desire to see ever-improving standards in coloproctology throughout Europe. By including contributions from authors across Europe, the book provides a great breadth of knowledge and reflects diversity of clinical practice. The manual provides surgical trainees with a comprehensive and condensed guide to the knowledge required for the European Board of Surgery Qualification (EBSQ) examination. It will also be a valuable aid to the many practicing coloproctologists across Europe and beyond who undertake continuing professional development and a useful source of information for researchers and clinicians in allied disciplines.
Keywords: Medicine.; Proctology.; Rectum -- Surgery.; elektronické knihy; electronic books